RESPON MUSLIM INDONESIA TERHADAP GERAKAN ISLAMISME DI TIMUR TENGAH: KASUS HAMAS DAN KONFLIK PALESTINA - Mulawarman Hannase (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2016)
This paper will examine how the Indonesian Muslim community which consist many streams of religious and social organizations to respond the crisis that involved recently in the Gaza Strip involving Hamas Islamism group. The main issue highlighted in this paper is whether Hamas has network in Indonesia? How the influence of Hamas network in Indonesia towards the development of Islamic fundamentalist thought in Indonesia? Is the Muslim community in Indonesia has the same view in addressing the conflict in the Gaza Strip?This article will use two approaches; the theological and political approach. Theological approach is used to see similarity of the doctrine espoused byHamas with some Islamists in Indonesia. Moreover, this approach is also used to distinguish between Hamas ideological doctrine with the view of other Islamist groups grown today. While political approaches used to answer the question how the political support of the Indonesian people against the Israeli Palestinian conflict, in particular the conflict between Hamas and Israel. Based on review of the above problems, it can be found that from an ideological perspective, Hamas has a strong network in various countries, including Indonesia. Whereas the model of Indonesian Muslims support to the Gaza crisis, at least occurs in three forms: pan-Islamism, diplomatic support and humanitarian support